Molecular Biology Review: Tumor Suppressor Gene (P53) as Target for Cancer Gene Therapy - N L P Indi Dharmayanti (Indonesian Center for Animal Research and Development, 2003)
Cancer cells are accumulation of numerous genetic alteration that contribute to tumorigenesis, tumor progression and chemotherapeutic drug resistance. Most of these alteration affect the regulation of the cell cycle. In normal cells, a balance is achieved between proliferation and cell death by tightly regulating the progression through the cell cycle with cell cycle with cellular checkpoints. The accumulation of genetic alterations also contributes to enhanced chemoresistance, resulting from the loss of the ability to respond to DNA damage. The detection of DNA damage is governed by tumor suppressor p53. Following DNA damage, p53 arrest the cell to allow time for repair, or if the damage is extensive enough, p53 initiates programmed cell death or apoptosis. Loss of these various molecular checkpoint has been found to underlie the development of many tumors because cell cycle progression becomes dysregulated. Therefore a major strategy in gene therapy for cancer has focused on replacing the tumor suppressors in cancer cells. p53-gene therapy remains the most important tumor suppressor strategy being developed and its combination with chemotherapy or radiotherapy may prove to be even more beneficial. However, p53 may not represent the ideal choice for gene therapy in all cancers. In tumor that overexpress MDM2 or have HPV16 E6, other tumor suppressors such as p21 may be more desirable targets of gene therapy because they can bypass the inactivation of p53. Several problem still need to be resolved. First, an efficient vector needs to be designed that cause prolonged high expression of the transduced gene while only targeting cancer cells. Second, further criteria need to be established in scheduling the decision about which tumor suppressor to employ for gene therapy. Key words: Tumor suppressor gene (p53), gene therapy, cancer